Al-Ashmawî dan Nalar Kritis Shariâat: Menemukan Kembali Dimensi yang Hilang dari Wacana Shariâat Islam - Hanafi, Yusuf (Program Pascasarjana UIN Sunan Ampel Surabaya, 2008)
Shariâah is the heart of Islam because it handles the most fundamental aspects of the religion. Ironically however, Shariâah is the most misunderstood dimension of Islam. What we currently believe as Shariâah may not be Shariâah. And the reverse may be true that what we consider as non-Shariâah, may in fact be Shariâah. It is here that reconstructing our understanding concerning the true meaning of Shariâah becomes a matter of necessity. Having this in mind, we are interested in elaborating the critical views of al-Ashmawi on the notion of Shariâah hoping that this will help us to discover the missing âand yet the true- dimension of Shariâah. Al-Ashmawi on the whole, is critical against the jargon that only associates the Shariâah with its formalization and application.